Implementation of English Language Learning in the Elementary School Teacher Education Study Program of the Open University - Sibuea, Bismar; Silalahi, Mardin; Silalahi, Tiodora; Matondang, Marhaeni K D (Global Education Journal, 2025)
The challenges of education today are inevitable. The need for education which is part of the needs of life accompanied by increasingly sophisticated technological developments must of course go hand in hand to become an innovation for education. This study aims to see and describe clearly how the implementation of English language education for elementary school teacher education at the Open University. The research method used is a descriptive qualitative approach, in which the author is the key to the research who directly collects data in the field through observation, interviews with informants, then collects documentation related to the research. The results of the study show that the implementation of English education at UT has been designed with the aim of equipping students with basic English language skills that are relevant to the context of elementary education. Learning is carried out through an online learning system that combines independent learning with printed and digital modules and online tutorials (TUTON). Technology, such as the UT LMS platform and video and audio media, is the main means of delivering material and evaluation. Learning evaluation is carried out through individual assignments, discussion forums, quizzes, mid-term exams, final semester exams, as well as teaching practices and Final Program Assignments.